2017
DOI: 10.1097/bot.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Radiation Dose in Computed Tomography of Articular Fractures

Abstract: The results of this study show no significant difference when evaluating current standard and low-dose CT scans using less than one-half the amount of exposure. This suggests that in complex extremity fractures, a new CT protocol may potentially be used. Our initial data show promise that we may retain satisfactory imaging to formulate a treatment plan while also reducing the collective radiation burden to the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Clinical studies have shown that implementation of ASIR-V can decrease the mean RD between 34 and 35% while maintaining image quality [13,14]. Previously reported mean RD for low-dose CT evaluation of fractures of the peripheral skeleton has been in the range of 10-800 μSv [12,[15][16][17][18] and for cone-beam CT (CBCT) in the range of 0.9-14.3 μSv [19]. Our ULD-CT protocol has, to our knowledge, the lowest reported mean RD (0.59 μSv) for the peripheral skeleton in the literature, corresponding to around 1.7 h of exposure to background radiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that implementation of ASIR-V can decrease the mean RD between 34 and 35% while maintaining image quality [13,14]. Previously reported mean RD for low-dose CT evaluation of fractures of the peripheral skeleton has been in the range of 10-800 μSv [12,[15][16][17][18] and for cone-beam CT (CBCT) in the range of 0.9-14.3 μSv [19]. Our ULD-CT protocol has, to our knowledge, the lowest reported mean RD (0.59 μSv) for the peripheral skeleton in the literature, corresponding to around 1.7 h of exposure to background radiation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Derived from similar studies that evaluated injuries about the knee and ankle, 5,6 five different protocols were created, all of which kept the kVp value constant at 120, and varied by sequentially lowered mAs values of 75, 60, 45, 30, and 15. To define these sequentially lowered radiation doses, we calculated the average amount of radiation (using DLP) used in 20 patient knee CTs performed within the last year at our institution.…”
Section: Ct Protocol Developmentmentioning
confidence: 99%
“…A delicate balance exists between image quality and radiation exposure in the evaluation of orthopaedic trauma patients. [1][2][3][4][5][6][7] The ability to characterize unique fracture patterns and musculoskeletal anatomy has significantly im-proved with advances in computed tomography (CT) techniques. 1,[8][9][10][11][12][13][14][15] However, the collective radiation burden sustained by the population has also increased substantially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Thus, there is a growing awareness of the need to use the lowest possible radiation dose level that is capable of providing appropriate diagnostic information, also known as the ALARA principle (As Low As Reasonably Achievable). 9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] CT is the gold standard for diagnosing fractures, 10,[25][26][27] characterizing them in greater detail, identifying hidden fractures and showing incomplete union. 27,28 In musculoskeletal radiology, lowdose CT has shown good results in studies with pre and postoperative scoliosis evaluations, as well as in diagnosing lytic injuries and fractures in patients with multiple myeloma.…”
mentioning
confidence: 99%